Use of Lectins in Inhibiting the Adhesion of Pasteurella multocida - Carrillo Lamus, Magda Patricia (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2013)
The first step of infection is the adhesion of pathogens to target cells. This feature not only allows them to penetrate and deploy offensive strategies to initiate colonization, but to contribute to their protection and preservation against both the immunological and mechanical defense mechanisms of the host. This process is conducted largely by the interaction of lectins, which are proteins of non-immune origin with the ability to recognize and bind carbohydrates. This mechanism has been reported for many microorganisms such as bacteria and viruses. In the particular case of Pasteurella multocida, which is a Gram-negative, opportunistic pathogen bacterium that starts the infection in the respiratory epithelium of many animals, lectin substances have been described on its surface, such as type IV fimbria, and carbohydrates such as lipopolysaccharide or the capsule that recognizes carbohydrates and lectins, respectively, on the surface of epithelial cells of the trachea, a circumstance that allows it to adhere and escape the mucociliary effect. Seeing as, to most of these microorganisms —including P. multocida—the decreased susceptibility to antibacterial agents and the effectiveness of vaccines is evident, new therapeutic and prophylactic tactics have been sought in order to interrupt pathogenic infection by blocking the carbohydrate-lectin bond by competition, where the union of the microorganism to the tissue and, therefore, the infection, is diminished.